Applying User-centered Design to Discovery Layer Evaluation in the Law Library. Issue 1 (3rd April 2019) - Uhl, Scott
Abstract: Usability and user experience are an important factor in the overall value of products and services offered by law libraries. User experience evaluation tools can help librarians make better decisions for their users when choosing databases to purchase or subscribe to, designing a library website, or selecting and implementing discovery layers. This article describes an array of evaluation tools and discusses how and when they can be implemented in the law library context.